Characterization of potassium glycinate for carbon dioxide absorption purposes - A. F. Portugal (2007)
Aqueous solutions of potassium glycinate were characterized for carbon dioxide absorption purposes. Density and viscosity of these solutions, with concentrations ranging from 0.1 to 3 M, were determined at temperatures from 293 to 313 K. Diffusivity of CO2 in solution was estimated applying the modified Stokes-Einstein relation. Solubilities of N2O at the same temperatures and concentrations were measured and the ion specific parameter based on Schumpe's model was determined for the glycinate anion; the solubilities of CO2 in these solutions were then computed. The reaction kinetics of CO2 in the aqueous solution of potassium glycinate was determined at 293, 298 and 303 K using a stirred cell reactor. The results were interpreted using the DeCoursey equation for the calculation of the enhancement factor. The rate of absorption as a function of the temperature and solution concentration for the conditions studied was found to be given by the following expression: -r(CO2) = 2.42 x 10(16) exp (-8544/T) exp(0.44C(S))CSCCO2.